ANALISIS PRODUKSI BAWANG MERAH LOKAL PALU DI LIMOYO KELURAHAN PANTOLOAN BOYA KECAMATAN TAWAELI - Nurfadillah, Nurfadillah; Muis, Abdul; Tangkesalu, Dance (AGROTEKBIS, 2018)
This study aimed to determine the effect of land area size, seeds, fertilizers and labors on local Palu shallot production in Limoyo of  Pantoloan Boya village, Tawaeli sub district. Samples of 32 people were selected from 120local Palu shallot farmers in Limoyo using a Simple Random Sampling technique. Data were analyzed using Cobb-Douglas production analysis. The analysis concludes that production factors such as land area size, seeds, fertilizers and labor simultan eously has a significant effect on local Palu shallot production with F-count value was 34.07 > F-tablevalue (2.73) at the α level of 5%. The result of t-test shows that partially land area and seed has significant effect on local Palu shallot production at the α level of 5%. While fertilizer and labor had no significant effecton local Palu shallot production at theα level of 5%. Keywords: Palu shallot, and  Production,